2002
DOI: 10.1017/s003060530200025x
|View full text |Cite
|
Sign up to set email alerts
|

Use of tracking strips and automatic cameras for detecting Critically Endangered Jerdon's coursers Rhinoptilus bitorquatus in scrub jungle in Andhra Pradesh, India

Abstract: Jerdon's courser Rhinoptilus bitorquatus is a Jerdon's courser has not yet been detected. The use of tracking strips carries a small risk of misidentification of nocturnal cursorial bird that is now only known from a small area of scrub jungle in Andhra Pradesh, India. Its footprints of other species, especially yellow-wattled lapwing Vanellus malarbaricus, as those of Jerdon's courser, population size, distribution and habitat requirements are poorly known because of its elusive habits. We but has the advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Tracking has the potential disadvantage that the tracks of other bird species, most probably yellow‐wattled lapwing Vanellus malarbaricus Boddaert and chestnut‐bellied sandgrouse Pterocles exustus Temminck, might be mistaken for those of Jerdon's courser. However, confusion with lapwing footprints is unlikely in this study because the overlap in footprint characteristics between the two species is small (Jeganathan et al . 2002) and yellow‐wattled lapwings are rarely seen in the types of habitat included in our survey.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Tracking has the potential disadvantage that the tracks of other bird species, most probably yellow‐wattled lapwing Vanellus malarbaricus Boddaert and chestnut‐bellied sandgrouse Pterocles exustus Temminck, might be mistaken for those of Jerdon's courser. However, confusion with lapwing footprints is unlikely in this study because the overlap in footprint characteristics between the two species is small (Jeganathan et al . 2002) and yellow‐wattled lapwings are rarely seen in the types of habitat included in our survey.…”
Section: Discussionmentioning
confidence: 95%
“…None was seen in our study blocks, even though lapwings are diurnal and easy to see in their preferred, more open habitats. Chestnut‐bellied sandgrouse were often seen in the study areas, but close examination of footprints of this species allows accurate identification (Jeganathan et al . 2002; P. Jeganathan & R.E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by several large rivers such as the Godavari (1,465km), Krishna (1,400km) and Cauvery (800km) flowing east into the Bay of Bengal (Mani 2012). The Eastern Ghats lansdcape is a treasure trove of biodiversity where several species endemic to the landscape such as the Golden Gecko Calodactyloides aureus (Daniel et al 1986;Javed et al 2007), the Jeypore Ground Gecko Geckoella jeyporensis (Agarwal et al 2012), the Slender Loris (Singh et al 2000) and the Critically Endangered Jerdon's Courser Rhinoptilus bitorquatus (Jeganathan et al 2002) have been reported. The northern section of the Eastern Ghats in particular contains extensive stretches of moist deciduous and semi-evergreen forests harboring high biodiversity and several rare species (Javed et al 2007;Seetharamaraju et al 2009;Sreekar & Srinivasulu 2010); however, there is no published baseline information on the mammal diversity of the northern Eastern Ghats, and there are currently no updated lists of mammals for the landscape.…”
Section: Mammals Of Papikondamentioning
confidence: 99%
“…Jerdon's Courser can be detected using playback surveys to elicit calls (Jeganathan & Wotton 2004) and tracking strips to record footprints (Jeganathan et al . 2002).…”
mentioning
confidence: 99%